Who runs first to the bank? - Hubert János Kiss; Ismael Rodríguez-Lara; Alfonso Rosa-Garcia (Hungarian Academy of Sciences, Institute of Economics, 2018)
We study how lines form endogenously in front of banks when depositors differ in their liquidity needs. Our model has two stages. In the first one, depositors choose the level of costly effort they want to exert to arrive early at the bank which determines the order of decisions. In the second stage, depositors decide whether to withdraw or to keep the funds deposited. We consider two different informational environments (simultaneous and sequential) that differ in whether or not depositors can observe the decision of others during the second stage of the game. We show theoretically that the informational environment affects the emergence of bank runs and thus should influence the willingness to rush to the bank. We test the predictions in the lab, where we gather extensive data on individual traits to account for depositors' heterogeneity; e.g. socio-demographics, uncertainty attitudes or personality traits. We find no significant differences in the costly effort to arrive early at the bank neither across the informational environments, nor according to the liquidity needs of the depositors. In the sequential environment, some depositors rush to the bank because they are irrational and do not recognize the benefits of observability in fostering the coordination on the no-bank run outcome. There is also evidence that some depositors rush to keep their funds deposited and to facilitate coordination on the efficient outcome. Finally, we document that loss aversion is an important factor in the formation of the line.
Keywords: C91; D03; D8; G02; J16; 330; bank runs; coordination problems; endogenous formation of lines; loss aversion; risk aversion; experimental economics; game theory; sequential games; simultaneous games